Arts and aesthetics in a globalizing world - Kaur, Raminder; Dave Mukherji, Parul (Bloomsbury Academic, 2014)
"Art and Aesthetics in a Globalizing World investigates art and aesthetics in their widest senses and experiences, from a variety of perspectives branching from the metaphysical to the political. Moving beyond art as an expression of the inner mind and invention of the individual self, the volume bridges the gap between changing perceptions of contemporary art and aesthetics, and maps globalising currents in a number of contexts and regions. The volume includes an impressive variety of case studies offered by established leaders in the field and original and emergent scholarly talent covering areas in India, Nepal, Indonesia, Iran, Russia, Rwanda and Germany as well as providing transnational or diasporic perspectives. From the contradictory demands made on successful artists from the south in the global art world such as Anish Kapoor, to images of war and puppetry created by female political prisoners, the volume compels creative and political interpretations of the ever-changing and globalizing terrain of arts and aesthetics. Art and Aesthetics in a Globalizing World will be important reading for students and scholars of the anthropology of art, art, and art history, and media, film and cultural studies."--
Includes bibliographical references and index